PENGARUH TEKNIK RELAKSASI HYPNOBIRTHING TERHADAP PENURUNAN RASA NYERI KALA I PERSALINAN NORMAL PADA PRIMIPARA DI RUMAH SEHAT KASIH BUNDA KEC MEDAN SELAYANG TAHUN 2019 - Eka Sriwahyuni; Andani Barus; Megawati Sinambela (JURNAL ILMIAH DHDT - KEBIDANAN, 2019)
Hypnobirthing is one of the hypnosis techniques (self-hypnosis), which is a natural effort to instillpositive intentions/suggestions into the soul / subconscious mind during pregnancy and childbirthpreparation. Primipara is a woman who gives birth for the first time and tends to experience moreintense pain than multiparas. The only practice of midwives in the city of Medan that useshypnobirthing is Rumah Sehat Kasih Bunda. This study was conducted to determine the effect ofhypnobirthing relaxation techniques on decreasing pain in the first stage of normal labor inprimipara in Rumah Sehat Kasih Bunda in 2019. This study was a Quasi Experiment with thePretest-Postest design with a control group. The number of samples was ten people, namely fiverespondents as experiments and five respondents as controls. The sampling procedure uses anaccidental sampling technique — retrieval of data using questionnaires. Data analysis carried outby univariate and bivariate with the t-independent test. The results showed that there was aneffect of hypnobirthing relaxation techniques on normal labor because there was a decrease inpain in the first stage of normal labor in primiparas after hypnobirthing did. We recommend thatpregnant women and mothers who will give birth take classes for pregnant women who not onlyfocus on pregnancy but also about hypnobirthing and are advised to use hypnobirthing relaxationtechniques to reduce pain in the first stage of labor.